Laporan Kasus: Penyakit Paru Obstruktif Kronis - Ananda Fadilah; Dian Yulianti; Deva Bachtiar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
COPD (Chronic Obstructive Pulmonary Disease) is a chronic respiratory disease that is preventable and treatable, characterized by progressive and persistent airflow obstruction, associated with an inflammatory response in the airways due to exposure to certain gases or particles. COPD is diagnosed in patients with a history of worsening shortness of breath during physical activity and with advancing age, accompanied by productive cough, or in those with a similar history and a Brinkman Index score of ?200. The prevalence of COPD increases significantly with age, peaking in individuals in their 60s. It is notably higher in men compared to women. A 2013 study of smokers aged over 40 years showed that the prevalence of COPD in Jakarta, Banten, and West Java was 5.4% in urban areas and 7.2% in rural areas. This paper discusses the case of a 50-year-old male diagnosed with COPD. Based on the data obtained, the patient should receive appropriate management for COPD, including bronchodilator therapy accompanied by antibiotics. The patient’s condition will be evaluated periodically to monitor disease progression. Additionally, the patient will receive education to help him understand the risks associated with his condition.